IDENTIFICATION OF POTENTIAL INTEGRATION BETWEEN ACTIVITY CENTERS (NODES) IN THE BANDAR LAMPUNG URBAN AREA (Jurnal Arsitektur ARCADE, 2026)
The lack of Public Open Spaces (POS) in Bandar Lampung is still a fundamental challenge in achieving sustainable urban development. The city also shows a polycentric pattern, where various activity centers grow in different districts, but this is not yet supported by proper planning or spatial integration. At the same time, understanding how communities actually use urban spaces is important to see how these areas function in everyday life. This study aims to develop a concept for urban nodes in Bandar Lampung that is adaptive, integrated, and responsive by considering community behavior. The methods used include mapping observations (to identify activity center points) and questionnaires (to understand user behavior in POS). The results show that among the four districts studied, Enggal District has the strongest potential to serve as a primary node that can integrate other surrounding nodes.
Keywords: Public Open Space, Urban Nodes, Community Behavior, Integrated Development